The capability enhancement of aluminium casting process by application of the novel CRIMSON method - Dai, Xiaojun; Jolly, Mark R.; Zeng, Binxu (Wiley, 2011)
The conventional foundry not only frequently uses batch melting, where the aluminium alloys are melted and held in a furnace for long time, sometimes as long as a complete shift, but also uses the gravity sand casting process where the molten aluminium alloys are transferred using a ladle from furnace to pour station and are poured into a mould. During the filling of the mould, the turbulent nature of the liquid metal gives rise to massive entrainment of the surface oxide films which are the subsequently trapped into the liquid and act as micro cracks. Also the long exposure time of the liquid surface to the surrounding environment during melting, transferring and filling will increase the level of hydrogen absorption from the atmosphere. The abovementioned factors are often the main reasons for casting defect generation. In this paper the novel CRIMSON aluminium casting method is introduced which has a number of advantages. Instead of gravity filling method, it uses the single shot upcasting method to realize the rapid melting and rapid counter-gravity-filling mould operations which reduce the contact time between the melt and environment thus reducing the possibility of defect generation. Another advantage is the drastic reduction of energy consumption due to shortened melting and filling time. A simulation software, FLOW-3D, is used to compare this new method with the conventional gravity casting process. A tensile bar case is used as a sample to simulate the filling process.
Keywords: aluminium casting process; CRIMSON; melting; oxide film